KESIAPAN TATA USAHA SEKOLAH DALAM MENGHADAPI ERA ADMINISTRASI DIGITAL: STUDI KUALITATIF DI MAS GUPPI SAMATA - Busaeri, Nurul Qalbiah; Windiyani, Ayu; Sahram, Elsa Arifah (Educational Leadership: Jurnal Manajemen Pendidikan, 2026)
Digital transformation in school administration demands greater effectiveness, Digital transformation in school administration requires increasing the effectiveness and quality of services, but the readiness of administrative personnel as the main implementers still faces various obstacles. This study aims to analyze the readiness of school administration in facing the era of digital administration at MAS Guppi Samata, using a descriptive qualitative approach through interviews, observations, and documentation with the subject of the Head of Administration. The results of the study show that administrative readiness is not optimal, marked by low digital competence, lack of continuous training, limited infrastructure and systems that have not been integrated, as well as limited manpower and funding. However, the madrasah has shown its commitment through the development plan of a barcode-based letter and student card management application. Different from previous research that focused on system implementation or digitalization effectiveness in general, this study reveals the relationship between human resource readiness, infrastructure, management support, and funding as determining factors for the success of digital administration transformation in madrasas, as well as being the basis for the formulation of policies to strengthen digital administration in Islamic educational institutions.